Tile Ceremony In The First Abbasid Era(132-232هـ/ 750-850م) - abbass, randa (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This study aims to highlight the Abbasid court ceremony as it represents all forms of physical and symbols, customs and norms that reflect the power of the Abbasid caliph.vkd study addressed the the palaces of the caliphs and what the purpose of Anchaehabaladafah to talk about style any dress caliphs who represents the greatness of king Alabasi kzlk study showed the presence of other manifestations annexed power represented Bisharat caliphate and the King,which developed and updated by the Abbasids Kalqdab and burda Media virtue of openness to all the Sasanian and Byzantine civilizations and even Islamic.